Evaluation of proximity of mandibular molars and second premolar to inferior alveolar nerve canal among central Indians: A cone-beam computed tomographic retrospective study - Hemalatha Hiremath; Rolly Agarwal; Vishwanath Hiremath; Tushar Phulambrikar (Wolters Kluwer Medknow Publications, 2016)
Context: A study was done to assess the average distances of root apices of mandibular first molar, second molar, and second premolar to inferior alveolar nerve canal (IANC), among males and females in central India. Materials and Methods: High-resolution full-volume cone-beam computed tomography (CBCT) scans were obtained from the radiology database at the Sri Aurobindo College of Dentistry, Indore. After scrutinizing the database, CBCT of 40 males and 40 females that conformed to the inclusion and exclusion criteria were selected for the study. Results: All the data were analyzed using SPSS, Version 16. Descriptive statistics of the variables and measurements are presented using Students t-test (paired and unpaired), and correlation between age was tabled by Karl Pearson's correlation coefficient method. Conclusion: For the second premolar, the average distance to the IANC was 0.88-13.03 mm for males and 0.00-5.49 mm for females. The average distance of IANC to the mesial root apex of first molar was 1.46-13.23 mm for males and 0.93-8.03 mm for females. For the second molar, the average distance was 1.31-14.71 mm for males and 0.00-6.91 mm for females (values on left side were shorter as compared to right side). In the overall population, only second molar exhibited significant difference in the distance from root apex to IANC when compared bilaterally. In addition to gender differences, age-related differences were found to be significant for the first molar on left side and second molar on the right side of the population (P< 0.05).